SELF-DIRECTED LEARNING WITH YOUTUBE: ENHANCING LISTENING SKILLS ON STUDENTS OF ENGLISH EDUCATION STUDY PROGRAM - Christmas Prasetia Ate; Agustinho da Conceição Anuno; Muliani Muliani (Universitas Citra Bangsa, 2025)
This qualitative study examines the use of YouTube as a tool for self-directed listening practice among 19 sixth-semester English Education students at Citra Bangsa University, Indonesia. Through semi-structured interviews, reflective journals, and usage observations, the research explores how learners engage with YouTube's features to enhance listening skills, the perceived benefits, and the challenges encountered. Findings indicate that students actively utilize YouTube's playback controls, subtitles, and content diversity to support autonomous learning, reporting improved comprehension of natural speech, better accent recognition, and expanded vocabulary. However, significant barriers emerged, including content discoverability difficulties, platform distractions, and technological limitations. The study highlights YouTube's dual role as both an empowering resource for authentic language exposure and a potentially disruptive medium requiring careful navigation. It reveals that while the platform aligns well with principles of self-directed learning (SDL), its effectiveness depends on institutional support and digital literacy training. Key implications suggest the need for structured guidance in material selection, curated playlists, and strategies to minimize distractions. The research contributes to the growing discourse on technology-enhanced language learning by providing insights from the Indonesian EFL context, where digital resources are increasingly adopted despite infrastructure challenges. Recommendations include integrating YouTube into formal curricula with scaffolding mechanisms to optimize its educational potential while addressing local constraints.